Lyapunov-based control for three-phase PWM ac/dc voltage-source converters - Komurcugil, H; Kukrer, O (IEEE-Inst Electrical Electronics Engineers Inc, 1998)
The three-phase pulsewidth modulation (PWM) ac/dc voltage-source converter with the control laws proposed so far is not only unstable against large-signal disturbances, but also has the problem that its stability depends on the circuit parameters such as the de-output capacitance. This paper describes a new control law based on Lyapunov's stability theory. It is shown that the converter can be stabilized globally for handling large-signal disturbances. The resulting closed-loop system not only guarantees a sufficient stability region (independent of the circuit parameters) in the state space, but also exhibits good transient response both in the rectifying and regenerating modes. Also, a new simulation technique is introduced,which increases the speed of the simulation process considerably. Computer simulations are presented to confirm the effectiveness of the proposed control strategy and the validity of the simulation technique. Experimental results are also presented to verify the theoretical and simulation studies.
Keywords: Lyapunov's direct method; space-vector PWM; three-phase ac/dc converters